The Effect of Giving Avocado Fruit (Persea Americana) and Honey on Hemoglobin Levels among Trimester III Pregnant Women with Anemia - Bunga Tiara Carolin; Rukmaini; Silferia Liester Maulina Situmorang (KHD Production, 2023)
Anemia is a health problem in pregnant women with a high prevalence which can have an impact on maternal and fetal death. Pregnancy can aggravate the incidence of anemia due to hemodilution. Providing Fe tablets and education on good nutrition can prevent anemia. Avocados and honey are foods that contain Fe and Vitamin C which can increase blood hemoglobin levels to prevent anemia. This study aims to determine the effect of avocado and honey on blood hemoglobin levels in third-trimester pregnant women in the intervention group and control group and to determine the average hemoglobin levels before and after treatment in the experimental group and control group. The research design used was quasi-experimental research with a pre and post-test design with the control group. The sample in this study was 30 respondents in the third trimester of pregnancy, consisting of 15 respondents in the control group and 15 respondents in the intervention group. The sampling technique uses a purposive sampling technique. The research instrument used a hemoglobin examination observation sheet. Data were analyzed using paired samples t-test and independent t-test. The results of the study showed that there was a significant average difference in hemoglobin levels before and after being given avocado in the intervention group, p=0.000. Avocados and honey can increase hemoglobin levels in third-trimester pregnant women. It is hoped that avocados and honey can be applied as nutritional education in health services.